Fiber-based electronics for sensing and energy harvesting - Zhang, Haozhe (Nanyang Technological University, 2024)
The popularity of fiber-based functionalities has surged in recent decades due to their excellent flexibility, being lightweight, and excellent performance. Among these applications, diverse functions such as energy harvesting, thermal sensing, and logic operation are crucial in the realization of fully integrated electronic textile systems. These advances in fiber-based devices can be attributed to the development of multi-functional materials, structures, and fabrication methods. Thermal drawing, coating, and spinning become the mainstream for realizing the integration of multi-materials and unique structures. These processes are utilized in our work to achieve a diverse range of fiber-based functionalities. First, a thermal drawing assisted organic electrochemical transistor (OECT) is fabricated with a wet-spun stretchable conductive polymer fiber and a flexible elastomer preform. This drawn fiber presents excellent uniformity, flexibility, and stretchability. The OECT provides a high ON/OFF ratio and output current under a small gate voltage bias, enabling the construction of fiber-based logic circuits. Additionally, it is connected to a thermally drawn capacitor to achieve a transistor-capacitor structure, showcasing the capability for data storage. These results indicate a pathway for the large-scale fabrication of extended fiber-based devices for electronic textile systems. Next, a preform containing insulating polymer cladding, polymer electrodes, and thermoelectric material core undergoes a thermally drawing process to produce long and uniform thermoelectric fibers for thermal sensing. The fiber can work in room temperature range with high sensitivity and flexibility. Notably, the fiber shows sensing capabilities in both fiber length and width direction. These properties exhibit the potential for applications in wearable sensory systems. A single thermoelectric fiber is used for thermal sensors in the room temperature range. The successful construction of a single TE fiber provides insights into achieving wearable TE devices by weaving multiple long fibers into fabrics to obtain an accumulated effect, making it a strong competitor for next-generation large-scale thermal sensing fabrics. Last, a high-performance fiber-shaped Zn ion battery integrated with a strain sensor is reported. The high electrochemical active surface and fast charge transfer of α-MnO2 nanoflowers provide a remarkable capacity, admirable electrochemical durability, and a desirable energy density.Moreover, by cascading or parallelly connecting the batteries, different voltage outputs can be offered to easily power an electronic watch and LEDs. Additionally, this fiber-shaped Zn ion battery presents outstanding flexibility. It is also integrated with CNT/PDMS composites to charge the strain sensing system for human body motion detection. The successful construction of flexible fiber-shaped Zn ion batteries integrated with strain sensors is a promising competitor in achieving multifunctional energy-storage devices for next-generation wearable electronics.